A pragmatic group sequential, placebo-controlled, randomised trial to determine the effectiveness of glyceryl trinitrate for retained placenta (GOT-IT): a study protocol. Issue 9 (18th September 2017) - Denison, Fiona C; Norrie, John; Lawton, Julia; Norman, Jane E; Scotland, Graham; McPherson, Gladys C; McDonald, Alison; Forrest, Mark; Hudson, Jemma; Brewin, Jane; Peace, Mathilde; Clarkson, Cynthia; et al.
Abstract : Introduction: A retained placenta is diagnosed when the placenta is not delivered following delivery of the baby. It is a major cause of postpartum haemorrhage and treated by the operative procedure of manual removal of placenta (MROP). Methods and analysis: The aim of this pragmatic, randomised, placebo-controlled, double-blind UK-wide trial, with an internal pilot and nested qualitative research to adjust strategies to refine delivery of the main trial, is to determine whether sublingual glyceryl trinitrate (GTN) is (or is not) clinically and cost-effective for (medical) management of retained placenta. The primary clinical outcome is need for MROP, defined as the placenta remaining undelivered 15 min poststudy treatment and/or being required within 15 min of treatment due to safety concerns. The primary safety outcome is measured blood loss between administration of treatment and transfer to the postnatal ward or other clinical area. The primary patient-sided outcome is satisfaction with treatment and a side effect profile. The primary economic outcome is net incremental costs (or cost savings) to the National Health Service of using GTN versus standard practice. Secondary outcomes are being measured over a range of clinical and economic domains. The primary outcomes will be analysed using linear models appropriate to the distribution of each outcome. Health service costs will be compared with multiple trial outcomes in a cost-consequence analysis of GTN versus standard practice. Ethics and dissemination: Ethical approval has been obtained from the North-East Newcastle & North Tyneside 2 Research Ethics Committee (13/NE/0339). Dissemination plans for the trial include the Health Technology Assessment Monograph, presentation at international scientific meetings and publication in high-impact, peer-reviewed journals. Trial registration number: ISCRTN88609453 ; Pre-results.